Composition and identification of pollen collected by stingless bee (Heterotrigona itama) in forested and coastal area of Terengganu, Malaysia - Suhaizan Lob,; Norezienda Afiffi,; Shamsul Bahri Abdul Razak,; Nurul Faziha Ibrahim,; Iffah Hazirah Mohd Nawi, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The aim of this study was to determine the composition and identify the pollen foraged by Heterotrigona itama in coastal and forested area over a period of nine months. The sampling has been conducted started from June 2016 until February 2017. Pollen composition obtained from the pollen basket of H. itama in coastal area and forested area of Terengganu was observed and recorded using optical microscope. Up until February, H. itama in coastal area had collected 14 different type of pollen, however only 10 types of pollen have been successfully identified. The identified pollen were Antigonan leptopus, Amaranthus tricolor, Hibiscus rosa-sinensis, Cucumis melo, Ixora coccinea, Tridax procumbens, Biden pilosa, Turnera subulata, Ixora javanica and Portula grandiflora which was the dominant pollen that has the highest percentage. Meanwhile H. itama in forested area has collected 15 different type of pollen with only 7 types of pollen have been successfully identified. The identified pollen were dominated by Asystasia gangetica followed by Biden pilosa, Antigonan leptopus, Reullia brittonia, Amaranthus tricolor, Hibiscus sabdariffa and Portulaca grandiflora. This observation could be useful for plants and H. itama conservation purposes and also in planning a suitable beescape for Meliponiculture in Malaysia.